Control of hair growth using long-pulsed alexandrite laser is an efficient and cost effective therapy for patients suffering from recurrent pilonidal disease. Issue 5 (July 2016) - Khan, Muhammad; Javed, Ammar; Govindan, Karthikeyan; Rafiq, Sadia; Thomas, Kay; Baker, Lynne; Kenealy, John
Abstract Pilonidal sinus (PNS) and its surgical management have a profound impact on hospital resources in terms of finances and productive man-hours. Surgical treatment has been the mainstay of treatment of both acute and chronic pilonidal sinus but recurrence is common. The control of hair growth in the sinus region plays an important role in preventing recurrence. Here, we discuss our experience of treating 19 patients suffering from recurrent pilonidal sinus with laser depilation and its long-term cost effectiveness. This is a retrospective study on patients who had recurrence of pilonidal sinus following multiple surgical treatments. They were treated using long-pulsed alexandrite laser for depilation in the sinus area, an outpatient procedure. Their clinical characteristics and outcomes were then evaluated. There was a significant reduction in hair density after laser treatment (p  < 0.001). The disease-free period after laser treatment was significantly longer than that one after surgical treatment (p  < 0.001). The average cost of repeated surgical treatment per disease-free month was significantly higher than that of laser treatment (p  < 0.001). Evidence suggests the role of natal cleft hair growth in the evolution of the pilonidal disease; therefore, control of hair growth should be considered as an adjunct to the initial treatment via surgery. Compared to surgical treatment of recurrences, laser depilation is an efficient and cost-effective method of preventing recurrence and reducing morbidity and loss of man-hours. We suggest that laser depilation of the pilonidal sinus should be funded by clinical commissioning groups.